Nitric Oxide-Releasing Polymeric Materials for Antimicrobial Applications: A Review - Fan Rong; Yizhang Tang; Tengjiao Wang; Tao Feng; Jiang Song; Peng Li; Wei Huang (MDPI AG, 2019)
Polymeric materials releasing nitric oxide have attracted significant attention for therapeutic use in recent years. As one of the gaseous signaling agents in eukaryotic cells, endogenously generated nitric oxide (NO) is also capable of regulating the behavior of bacteria as well as biofilm formation in many metabolic pathways. To overcome the drawbacks caused by the radical nature of NO, synthetic or natural polymers bearing NO releasing moiety have been prepared as nano-sized materials, coatings, and hydrogels. To successfully design these materials, the amount of NO released within a certain duration, the targeted pathogens and the trigger mechanisms upon external stimulation with light, temperature, and chemicals should be taken into consideration. Meanwhile, NO donors like S-nitrosothiols (RSNOs) and N-diazeniumdiolates (NONOates) have been widely utilized for developing antimicrobial polymeric agents through polymer-NO donor conjugation or physical encapsulation. In addition, antimicrobial materials with visible light responsive NO donor are also reported as strong and physiological friendly tools for rapid bacterial clearance. This review highlights approaches to delivery NO from different types of polymeric materials for combating diseases caused by pathogenic bacteria, which hopefully can inspire researchers facing common challenges in the coming ‘post-antibiotic’ era.